The Relationship Between Emotional Intelligence and Self-Control in Students of SMA Negeri M Makassar - parante, Maulia fajrianti; Alwi, Muhammad Ahkam (Polteknik Ilmu Pemasyarakatan, 2025)
This research focuses on the relationship between emotional intelligence and self-control in students at SMAN M Makassar. The problem raised in this research is the low level of self control among teenagers, which can have a negative impact on their behavior and academic achievement. Emotional intelligence, which includes the ability to recognize, understand and manage emotions, is expected to contribute to increasing students' self-control. Therefore, this research aims to find out whether there is a significant relationship between emotional intelligence and self-control in students. The method used in this research is a quantitative approach with a descriptive design. The research respondents consisted of 311 class XI students at SMAN M Makassar, who were chosen randomly. Data was collected through questionnaires measuring emotional intelligence and self-control, which have been tested for validity and reliability. Data analysis was carried out using the SPSS 27 program to test the proposed hypothesis. The research results show that there is a significant positive relationship between emotional intelligence and self-control in students, with a significance value of less than 0.05. The average student emotional intelligence score is 42 with a standard deviation of 9.333, while the average self-control score is 27 with a standard deviation of 6. These findings indicate that students with a higher level of emotional intelligence tend to have better self control.The implication of this research is to provide an overview of emotional intelegence and self control.